A proteomics investigation of 'immune priming' in Penaeus vannamei as shown by isobaric tags for relative and absolute quantification. Issue 117 (October 2021) - Zhai, Yufeng; Xu, Ruihang; He, Peimin; Jia, Rui
Abstract: Invertebrates are considered completely dependent on their innate immunity to defend themselves against pathogens as they lack an adaptive immunity. However, a growing body of evidence has indicated a specific acquired immunity called 'immune priming' may exist. The Pacific white shrimp, Penaeus vannamei is one of the most economically important shrimp species in the world. In the previous research, we investigated the hepatopancreas immune response of shrimp immunized with trans - vp28 gene Synechocystis sp. PCC6803 at the protein level. In this study, on the basis of the previous research, the shrimp were then challenged with WSSV, and hepatopancreas analyzed using isobaric tags for relative and absolute quantification (i TRAQ) labeling. In total, 308 differentially expressed proteins (DEPs) were identified including 84 upregulated and 224 downregulated. Upregulated proteins such as calmodulin B and calreticulin, and downregulated proteins such as calnexin, and signaling pathways like Ras, mTOR were differentially expressed in both studies. Data from this study are more significant than previous work and indicate increased sensitivity to WSSV after immunization with trans - vp28 gene Synechocystis sp. PCC6803. In addition, selected DEPs (upregulated: A0A3R7QHH6 and downregulated: A0A3R7PEF6, A0A3R7MGX8, A0A423TPJ4, and A0A3R7QCC2) were randomly analyzed using parallel reaction monitoring (PRM). These data preliminarily confirm immune priming in P. vannamei, and show that the initial stimulation with trans - vp28 gene Synechocystis sp. PCC6803 regulate P. vannamei immune responses and they provide shrimp with enhanced immune protection against secondary stimulation. Highlights: The data preliminarily confirm 'immune priming' in Penaeus vannamei . 5 DEPs identified in the i TRAQ analysis have been verified by PRM. The sensitivity to WSSV increased after immunization with the trans - vp28 gene Synechocystis sp. PCC6803.